An Analysis of Positive Culture Implementation in Supporting Students' Mental Health in Elementary Schools: Analisis Penerapan Budaya Positif dalam Mendukung Kesehatan Mental Siswa di Sekolah Dasar - Latifa, Latifa Nur Aini; Minsih, Minsih (JENIUS :Journal of Education Policy and Elementary Education Issues, 2025)
The increasing mental health disorders in students in Indonesia are currently a serious concern in the world of education, so effective strategies or handling are needed, one of which is through the implementation of a positive culture in schools. This study aims to analyze the implementation of a positive culture in maintaining students' mental health in elementary schools. This study uses a qualitative research method with data collection techniques through interviews, documentation, and observation. The research data analysis includes data reduction, data presentation, and conclusions. The subjects in this study were the school headmaster, five teachers, and twelve students representing grades 1 to 6. The results of the study indicate that implementing a positive culture program needs to pay attention to supporting factors for implementing a positive culture, such as the mental health conditions of students and the impact of implementing a positive culture in schools. The implications of the study indicate that the implementation of a positive culture in schools can create a conducive learning environment, maintain emotional stability, reduce anxiety, and form positive character in students.